Retinal and Circulating miRNAs in Age-Related Macular Degeneration: An In vivo Animal and Human Study - Romano, Giovanni L.; Platania, Chiara B. M.; Drago, Filippo; Salomone, Salvatore; Ragusa, Marco; Barbagallo, Cristina; Di Pietro, Cinzia; Purrello, Michele; Reibaldi, Michele; Avitabile, Teresio; Longo, Antonio; Bucolo, Claudio (Frontiers in Pharmacology, 2017)
Age related macular degeneration (AMD) is the leading cause of blindness among people aged 50 and over. Retinal deposition of amyloid-β (Aβ) aggregates in AMD patients has suggested a potential link between AMD and Alzheimer’s disease (AD). We have evaluated the differential retinal expression profile of miRNAs in a rat model of AMD elicited by Aβ. A serum profile of miRNAs in AMD patients has been also assessed using single TaqMan assay. Analysis of retina from rats intravitreally injected with Aβ revealed that miR-27a, miR-146a and miR-155 were up-regulated in comparison to control rats. Seven miRNA (miR-9, miR-23a, miR-27a, miR-34a, miR-126, miR-146a and miR-155) have been found to be dysregulated in serum of AMD patients in comparison to control group. Analysis of pathways has revealed that dysregulated miRNAs, both in the AMD animal model and in AMD patients, can target genes regulating pathways linked to neurodegeneration and inflammation, reinforcing the hypothesis that AMD is a protein misfolding disease similar to AD. In fact, miR-9, miR-23a, miR-27a, miR-34a, miR-146a, miR-155 have been found to be dysregulated both in AMD and AD. In conclusion, we suggest that miR-9, miR-23a, miR-27a, miR-34a, miR-146a, miR-155 represent potential biomarkers and new pharmacological targets for AMD.